Pengembangan Aplikasi Penunjang Pembelajaran Hewan Pada Buku Kelas IV Menggunakan Teknologi Augmented Reality - Djayanto, Ariya; Sijabat, Daniel Rudiaman (LPPM STIKI MALANG, 2022)
Education is a conscious and planned effort to create an atmosphere and learning process so that students are actively able to develop the potential that exists within themselves. However, during the Covid-19 pandemic, the learning process cannot be carried out in educational institutions or schools so that learning process is not optimal. One of the affected schools is SDN Purwantoro 2 Malang. One solution is to create applications using augmented reality technology that can support learning in accordance with what is applied in schools. Augmented Reality allows users to see two-dimensional or three-dimensional virtual objects used in the real world. with marker based tracking method. To introduce animals in 3D and display animations of these animals. The resulting application is android based and designed using Unity.